World's five worst invasive alien ant threats to biodiversity hotspots will not decrease significantly under future climatic conditions - Ming Li; Haoxiang Zhao; Zhenan Jin; Xiaoqing Xian; Jianyang Guo; Nianwan Yang; Rui Wang; Tao Jia; Wanxue Liu (Global Ecology and Conservation, 2025)
Invasive alien ants have reduced the populations of native species and even caused species extinction through direct predation, competition for resources and disruption of ecological relationships, posing a significant threat to global biodiversity hotspots. Identifying the potential geographic distribution of invasive ants and their areas of harm is critical to controlling and managing such species and reducing or avoiding damage to biodiversity. Here, ensemble models were used to predict the potential geographical distribution of the five most serious invasive alien ants and identify their areas of occupations and degrees of overlap with biodiversity hotspots under climate change. Furthermore, ecological niche differences and similarities among these ants were analyzed based on the niche hypervolume concept. Results indicate that the potential geographic distribution of five invasive ants overlap with biodiversity hotspots across the globe, including in Southern Asia, Southern Oceania, the Mediterranean region of Europe, Southern Africa, Southern North America, and South America. At least one ant was predicted to occur in 70 % of the total biodiversity hotspot area, and this trend will not significantly decrease under future climatic conditions. The higher the ecological niche similarity between these ants, the greater the overlapping area. Temperature and precipitation are the most important factors influencing their distribution. Countries worldwide should strengthen control and management of these five species in biodiversity hotspots, with the aim of reducing biodiversity loss.